Déconfiner les consciences par la systémique - Vitrac, Richard (Acta Europeana Systemica, 2020)
The Covid-19 pandemic has affected all of humanity. It was the first time that virtually all human beings on earth felt concerned by a particular event: a Chinese allegedly ate pangolin infected with a virus, causing an epidemic that has spread to all mankind. In the case of covid 19, virtually all humans have been informed by television and the internet. This made them stand together beyond any language, race or religion. However, this shared solidarity was based on the fear of illness and death. There was nothing to counterbalance this atavistic fear, other than, for some, a faith in a particular religion. On the contrary, systemic sciences, through Cognitive and Systemic Relativity (CSR), shows that fundamentally, our consciousness is immortal because it is not subject to time; it is inspatiotemporal or eternal. It only depends on each one to awaken his social consciousness (his ego) to its dimension of eternity, which corresponds to his EGO which is the Relativist Observer, pilot of the body. In addition, this individual awakening has the advantage of functioning as a positive pandemic, based on confidence in the source of life which is the Consciousness of Existing, the root of our EGO, and therefore also of our ego. This positive pandemic is based on a particular functioning which is the systemic entanglement of all the systems on earth since the EGO of all living systems on earth are in communion at all times. The conscious restoration of this communion of all EGO through trust in our individual EGO sets in motion the healing software of all systems on earth. This corresponds to the entry of humanity into what we might call universal brotherhood and which Teilhard de Chardin calls the noosphere.